Endogenous credit derivatives and bank behavior - Thilo Pausch (Deutsche Bundesbank, 2007)
Instruments for credit risk transfer arise endogenously from and interact with optimizing behavior of their users. This is particularly true with credit derivatives which are usually OTC contracts between banks as buyers and sellers of credit risk. Recent literature, however, does not account for this fact when analyzing the effects of these instruments on banking. The present paper closes this gap by explicitly modelling the market for credit derivatives and its interaction with banks? loan granting and deposit taking activities.
Keywords: D53; G21; G14; G11; D82; 330; credit risk; credit derivatives; bargaining; Bankrisiko; Kreditrisiko; Finanzderivat; Securitization; Bankbilanz; Portfolio-Management; Verhandlungstheorie; Theorie